Character Education and Students Social Behavior - Syamsu A. Kamaruddin (Journal of Education and Learning (EduLearn), 2012)
In an educational environment, in the form of character education program has been done both formally and informally. It's intended as one of the supporting ideas for follow-up in the form of design activities. Character education should basically refers to the vision and mission of the institution concerned. It shows the orientation of the two things in the character of the students are: aspects of human character and individual learners hallmark institution. In this paper, these two aspects is the author trying to ideas by referring to some other writings. The end result, the authors expect the birth of a design patent as early referral to spearhead a character development program learners.